Wielkopolskie nazwiska mieszkańców miast Ziem Zachodnich i Północnych - Skrodzki , Miłosz (Człowiek i Społeczeństwo, 2014)
The paper deals with the important, but not yet researched problem of new regions that emerged in the territories annexed to Poland after the Second World War. The removal of native inhabitants and settlement of Polish people created a radically new situation and new societies. Moreover, those large territories are varied, because people from different regions of prewar Poland came in different proportions. Then there is a need to investigate those areas and to point out new local communities. The best way to achieve this may be a research of surnames that are both strongly regional and relevant to social identity. Therefore the paper analyzes this criterion, counting the kinds of surnames originating from Greater Poland in major cities. Next it shows how those names are clustered into five distinct regions of the so-called West and North Territories.